Temporal dynamics of immune response following prolonged myocardial ischemia/reperfusion with and without cyclosporine A - Rusinkevich Vitali; Huang Yin; Chen Zhong-yan; Qiang Wu; Wang Yi-gang; Shi Yu-fang; Yang Huang-tian (Acta Pharmacologica Sinica; Vol 40, No 9 (September 2019): Acta Pharmacologica Sinica, 2019)
Understanding the dynamics of the immune response following late myocardial reperfusion is critical for the development of immunomodulatory therapy for myocardial infarction (MI). Cyclosporine A (CSA) possesses multiple therapeutic applications for MI, but its effects on the inﬂammation caused by acute MI are not clear. This study aimed to determine the dynamics of the immune response following myocardial ischemia/reperfusion (I/R) and the effects of CSA in a mouse model of prolonged myocardial ischemia designated to represent the human condition of late reperfusion. Adult C57BL/6 mice were subjected to 90 min of closed-chest myocardial I/R, which induced severe myocardial injury and excessive inﬂammation in the heart. Multicomponent analysis of the immune response caused by prolonged I/R revealed that the peak of cytokines/chemokines in the systemic circulation was synchronized with the maximal inﬂux of neutrophils and T-cells in the heart 1 day after MI. The peak of cytokine/chemokine secretion in the infarcted heart coincided with the maximal macrophage and natural killer cell inﬁltration on day 3 after MI. The cellular composition of the mediastinal lymph nodes changed similarly to that of the infarcted hearts. CSA (10 mg/kg/day) given after prolonged I/R impaired heart function, enlarged the resulting scar, and reduced heart vascularization. It did not change the content of immune cells in hearts exposed to prolonged I/R, but the levels of MCP-1 and MIP-1α (hearts) and IL-12 (hearts and serum) were signiﬁcantly reduced in the CSA-treated group in comparison to the untreated group, indicating alterations in immune cell function. Our ﬁndings provide new knowledge necessary for the development of immunomodulatory therapy targeting the immune response after prolonged myocardial ischemia/reperfusion.